PENGARUH KUALITAS LAYANAN DAN KOMPETENSI KARYAWAN TERHADAP KEPUASAN NASABAH ( Studi Kasus pada PT. Bank Tabungan Negara KCP Cibubur ) - Imam Wibowo (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
This research is based on competition for the struggle of customers in the banking world, thus demanding banking companies to compete to attract customers by constantly improving the quality of service and competence of employees who are considered as representative banking companies as a form of satisfaction fulfillment to its customers. The purpose of this study to determine how the influence of Service Quality and Employee Competence to customer satisfaction PT. Bank Tabungan Negara (Bank BTN), either partially or simultaneously. This research used qualitative method with descriptive research type. Sampling is used with non probability method of incidental sampling. The result of the simultaneous research on the quality of service and the competence of the employees is significant to customer satisfaction, partially the quality of service and employee competency also have a significant influence on customer satisfaction. Thus, banks should continue to improve the quality of service and employee competence in order to achieve customer satisfaction and attention to other aspects that add value from customer satisfaction.